Rust programming. (Pearson, 2023)
13 Hours of Video Instruction Rust programming for real-world applications. Rust Programming Part 2: Rust Advanced Concepts and Real-World Projects dives into professional Rust Programming concepts and practices while exploring hands-on skills through demonstrations of real-world applications. This hands-on course will look at how to organize Rust applications into functions, structures, and traits. You will learn how to use these techniques to achieve familiar object-oriented goals such as abstraction, encapsulation, inheritance, and polymorphism. You will also learn how Rust deals with important issues such as generic types and multithreading. A key objective of the course is for you to understand how to structure large applications properly in Rust. To this end, the course presents a detailed walkthrough of two complete real-world applications. The first application shows how to implement a CSV file parser, and the second application shows how to access a relational database. These applications were designed so you can learn the skills needed to start using Rust effectively and efficiently. Topics included in this course: Structuring Rust Code dives into the details of how to define functions closures (for example, lambdas), and structs. Advanced Rust Programming Concepts delves into defining traits, working with generics, and implementing multithreading and concurrency. You will also learn about dynamic heap allocation and integration with other programming languages. Real-World Rust in Action shows you how to use Rust for real-world applications. It focuses on how to implement a CSV file parser and how to use Rust to access a relational database. About the Instructor Andy Olsen is a freelance consultant, instructor, and developer with more than 30 years of experience in IT. Andy began his professional career as a C/C++ developer and transitioned into Java, C#, and other languages as the years passed. Andy is actively involved in a wide range of technologies including full-stack development, cloud native applications, data science, and more. Andy is passionate about technology education and runs training courses around the world across diverse market sectors. Skill Level : Intermediate Learn How To : Use object-oriented programming techniques Implement concurrency Explore additional Rust techniques Implement file handling Access a database Course requirement: None Who Should Take This Course : Developers that need to learn the details of how to write efficient and well-structured Rust applications People with prior OO language experience About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.